Onboard functional and molecular imaging: A design investigation for robotic multipinhole SPECT. Issue 1 (23rd December 2013) - Bowsher, James; Yan, Susu; Roper, Justin; Giles, William; Yin, Fang‐Fang
Abstract : Purpose: : Onboard imaging—currently performed primarily by x‐ray transmission modalities—is essential in modern radiation therapy. As radiation therapy moves toward personalized medicine, molecular imaging, which views individual gene expression, may also be important onboard. Nuclear medicine methods, such as single photon emission computed tomography (SPECT), are premier modalities for molecular imaging. The purpose of this study is to investigate a robotic multipinhole approach to onboard SPECT. Methods: : Computer‐aided design (CAD) studies were performed to assess the feasibility of maneuvering a robotic SPECT system about a patient in position for radiation therapy. In order to obtain fast, high‐quality SPECT images, a 49‐pinhole SPECT camera was designed which provides high sensitivity to photons emitted from an imaging region of interest. This multipinhole system was investigated by computer‐simulation studies. Seventeen hot spots 10 and 7 mm in diameter were placed in the breast region of a supine female phantom. Hot spot activity concentration was six times that of background. For the 49‐pinhole camera and a reference, more conventional, broad field‐of‐view (FOV) SPECT system, projection data were computer simulated for 4‐min scans and SPECT images were reconstructed. Hot‐spot localization was evaluated using a nonprewhitening forced‐choice numerical observer. Results: : The CAD simulation studies found that robots could maneuver SPECT cameras about patients in position for radiation therapy. In the imaging studies, most hot spots were apparent in the 49‐pinhole images. Average localization errors for 10‐mm‐ and 7‐mm‐diameter hot spots were 0.4 and 1.7 mm, respectively, for the 49‐pinhole system, and 3.1 and 5.7 mm, respectively, for the reference broad‐FOV system. Conclusions: : A robot could maneuver a multipinhole SPECT system about a patient in position for radiation therapy. The system could provide onboard functional and molecular imaging with 4‐min scan times.